Rapid detection of non-enterobacteriaceae directly from positive blood culture using fluorescent in situ hybridization - Wong, E. H.; Subramaniam, G.; Navaratnam, P.; Sekaran, S. D. (Medknow Publications, 2007)
Fluorescent in situ hybridization (FISH) was carried out using two different oligonucleotide probes specific for Pseudomonas spp. and Acinetobacter spp. These probes were tested against different organisms and were found to be highly specific. Sensitivity testing showed that the probes were able to detect as low as 10 3 CFU/mL. In addition, FISH was carried out directly on positive blood culture samples and the detection of microorganisms took less than 2 h. We believe that FISH is a rapid method that can be used as a routine laboratory diagnostic technique for the detection of Acinetobacter spp. and Pseudomonas spp. in clinical samples.